ENTREPRENEURSHIP TRAJECTORIES : entrepreneurial opportunities, business models, and firm ... performance. - MATRICANO, DIEGO (ELSEVIER ACADEMIC Press, 2020)
Entrepreneurship Trajectories: Entrepreneurial Opportunities, Business Models, and Firm Performance explores several entrepreneurship trajectories recognized by economists and entrepreneurs. It is not possible to talk about growth paths addressed by entrepreneurial ventures without recalling the business model and the type of entrepreneurial opportunity at their foundations. Diego Matricano assumes that the growth paths addressed by entrepreneurial ventures depend on both effective business models and promising opportunities. This pragmatic guide illuminates the entrepreneurial trajectories linking opportunities, business models, and growth paths, offering complete and nuanced views through its extensive use of case studies.